Influence of different types of transport on CO2 concentration - Kyrylenko, A. X. (ТДАТУ, 2021)
The results of our research showed that while transport emissions account for over 15% of global emissions and are expected to grow at a fast rate, there are still a lot of opportunities to make transport cleaner. Countries should further specify clear pathways and mobilize both public and private sectors to decarbonizing transport, soon, if they are going to avoid these dangers and seize the opportunities provided by 21st-century means of getting around.
Keywords: transport; emissions of CO2; carbon dioxide